Time-closed layer: a design principle for time-critical applications - Zedan, H. (Euromicro Workshop on Real Time, 1989: Proceedings, 1989)
A design principle, called time-closed layer, is developed for specifying and designing time-critical computing systems. The principle is based on the pseudoserialization to the systems activities. Each sub-activity is represented by a layer that satisfies both communication and time closedness properties. Operations such as SEQ, WHILE, ELSE, and ALT may be performed on layers. These operations allow the designer to manipulate layers in an algebraic manner. Formal semantics of the layers is also given using operational semantics approach to programming languages. The use of the time-closed layer is illustrated by designing a simple time-critical system which monitors and controls a reactor.< >